Perception of arousal in social anxiety: effects of false feedback during a social interaction. - Wild, J; Clark, D; Ehlers, A; McManus, F (2008)
Cognitive models suggest that during social interactions, socially anxious individuals direct their attention to internal cues of arousal and use this information to erroneously infer how they appear to others. High (N=36) and low (N=36) socially anxious adults had a conversation with a stooge, and were led to believe by false feedback that they were experiencing either an increase or decrease in arousal, or evaluating the comfort level of the feedback equipment. Compared to the other groups, participants who believed their arousal had increased, reported greater anxiety, poorer perceived performance, more physical cues of anxiety, and greater underestimation of their performance and overestimation of the visibility of their anxiety. The effects were not specific to participants with high social anxiety. Observers rated the behaviour of participants who believed that their arousal had decreased most favourably. The results have implications for the treatment of social phobia.